Nonlinear spring modelling approach for concrete edge breakout failure of shear loaded anchorages of arbitrary configurations. (15th March 2023) - Bokor, Boglárka; Sharma, Akanshu; Hofmann, Jan
Highlights: Spring modelling approach for anchorages against concrete edge failure is proposed. Modelling of anchor behavior through nonlinear shear springs. Tributary volume method to consider anchor pattern and multiple anchor rows. Influence of anchor and crack pattern, hole clearance, eccentricity is considered. Method equally applicable for rectangular and non-rectangular configurations. Abstract: The failure of anchorages placed close to the concrete edge and loaded in shear perpendicular towards the edge is often governed by the concrete edge breakout failure. Several assumptions are made in the current design methods to calculate the anchorage resistance, which simplify the calculations but may also lead to over-conservative or even unconservative design solutions. This paper presents a novel nonlinear spring modelling approach for the realistic evaluation of shear loaded anchor groups in case of concrete edge failure. The model follows a displacement-based approach and is developed on the basis of evaluation of a comprehensive experimental study carried out on shear loaded anchor groups. The basic philosophy follows the principles of the nonlinear spring model for the concrete cone failure mode of tension loaded anchorages, published earlier by the authors. In the nonlinear spring modelling approach for shear, it is assumed that the shear forces acting on a group are transferred from the base plate directly to the anchors. Nonlinear springs are used for modelling the anchor behavior to account for the distribution of forces among the anchors of the group. The nonlinear springs are provided to resist the forces acting in the loading direction and opposite to the loading direction, which might occur case of eccentric loading. While defining the properties of the nonlinear anchor springs, due consideration is given to the neighboring anchors through a tributary volume approach, to the vicinity of further edges and to the hole clearance. The friction between base plate and concrete is conservatively neglected. The postulates of the method are justified through a detailed evaluation of test results. The accuracy of the model is validated against a vast number of experimental results on anchor groups of arbitrary configurations.